Biomechanics of Dinosaurs: Studies by means of Engineering Techniques - Conti, Simone (2024)
Palaeontology is a science that has always been keen to introduce new methods in its research, since its dawn at the end of the XVIII sec. Computer-aided tests, such as Finite Element and Multibody Dynamic Analyses, were developed by engineers and their use grew greatly in the last decades, thanks to the increased availability of better and cheaper computers. The use of these methodologies has been rapidly spreading within the palaeontological community since the early 2000’s, granting access to test new hypotheses, without the risk of damaging the original specimens. However, palaeontological research is often bound to hypotheses that were tested in the past and to assumptions that are now considered old, despite the rapid growth in computational capacities of modern computers. Hence this thesis is born to implement updated methodologies, commonly used in aerospace engineering, in palaeontological research. With this project, I aim to review some hypotheses related to dinosaur behaviours taking into consideration both extinct and extant dinosaurs and revise some basic assumptions and conventions often applied in biomechanical research to create a solid starting point for the use of engineering methods. The study of the mechanical properties of ostrich bone materials revealed load-bearing adaptations. By use of Finite Element and Multibody Dynamic Analyses, I tested the dynamics of sauropod necks and tails, as well as the dynamics of the tail of stegosaur dinosaurs and the backbone of ornithopod dinosaurs. The study of stress resistance of soft tissue materials has been applied to palaeontological data and proved to be another useful method to verify palaeontological hypotheses regarding reasonable soft tissue reconstructions. The analyses of the ostrich leg bones revealed a polarization of the material properties as well as showing different mechanical material properties within the same bone, and load- bearing structural adaptations were observed in the femur and the tibia. The research conducted on dinosaur tails revealed that sauropod tails could not reach the speed of sound and that stegosaurid tails were valuable defensive weapons. The study conducted on the ornithopod caudal vertebrae showed a structural adaptation useful to generate efficient locomotion, yet making it more susceptible to external loading, thus explaining the high number of pathological remains found in the fossil record. The study conducted on the sauropod neck biomechanics tested different hypotheses of ligament arrangements and showed similar biomechanical adaptations in the morphology of mammal and sauropod cervical vertebrae. The study aimed to establish the feeding strategy of diplodocid sauropods proved that these animals were forced to feed on soft plant materials, due to the brittleness of their teeth, and the hypothesis of a rhamphotheca was tested as well, to measure its beneficial apport. In summary, the results obtained during this project revealed structural adaptations both in extant and extinct animals and proved that engineering methods can be successfully applied to resolve palaeontological-related tasks.